Simultaneous Voltammetric Detection of Carbaryl and Paraquat Pesticides on Graphene-Modified Boron-Doped Diamond Electrode - Aniela Pop; Florica Manea; Adriana Flueras; Joop Schoonman (Sensors, 2017)
Monitoring of pesticide residues in food, beverages, and the environment requires fast, versatile, and sensitive analyzing methods. Direct electrochemical detection of pesticides could represent an efficient solution. Adequate electrode material, electrochemical technique, and optimal operation parameters define the detection method for practical application. In this study, cyclic voltammetric and differential pulse voltammetric techniques were used in order to individually and simultaneously detect two pesticides, i.e., carbaryl (CR) and paraquat (PQ), from an acetate buffer solution and also from natural apple juice. A graphene-modified boron-doped diamond electrode, denoted BDDGR, was obtained and successfully applied in the simultaneous detection of CR and PQ pesticides, using the differential pulse voltammetric technique with remarkable electroanalytical parameters in terms of sensitivity: 33.27 μA μM−1 cm−2 for CR and 31.83 μA μM−1 cm−2 for PQ. These outstanding results obtained in the acetate buffer supporting electrolyte allowed us to simultaneously detect the targeted pesticides in natural apple juice.